Deposition of environmentally relevant nanoplastic models in sand during transport experiments. (September 2020) - Pradel, Alice; Hadri, Hind el; Desmet, Cloé; Ponti, Jessica; Reynaud, Stéphanie; Grassl, Bruno; Gigault, Julien
Abstract: Nanoplastics (NPTs) are defined as colloids that originated from the unintentional degradation of plastic debris. To understand the possible risks caused by NPTs, it is crucial to determine how they are transported and where they may finally accumulate. Unfortunately, although most sources of plastic are land-based, risk assessments concerning NPTs in the terrestrial environmental system (soils, aquifers, freshwater sediments, etc.) have been largely lacking compared to studies concerning NPTs in the marine system. Furthermore, an important limitation of environmental fate studies is that the NPT models used are questionable in terms of their environmental representativeness. This study describes the fate of different NPT models in a porous media under unfavorable (repulsive) conditions, according to their physical and chemical properties: average hydrodynamic diameters (200–460 nm), composition (polystyrene with additives or primary polystyrene) and shape (spherical or polymorphic). NPTs that more closely mimic environmental NPTs present an inhomogeneous shape (i.e., deviating from a sphere) and are more deposited in a sand column by an order of magnitude. This deposition was attributed in part to physical retention, as confirmed by the straining that occurred for the larger size fractions. Additionally, different Derjaguin-Landau-Verwey-Overbeek (DLVO) models -the extended DLVO (XDLVO) and a DLVO modified by surface element integration (SEI) method-suggest that the environmentally relevant NPT models may alter its orientation to diminish repulsion from the sand surface and may find enough kinetic energy to deposit in the primary energetic minimum. These results point to the importance of choosing environmentally relevant NPT models. Highlights: Nanoplastic models with environmentally relevant physicochemical properties were studied. Polymorphic (irregular and asymmetrical) particles are more likely to be trapped in porous media than spherical particles. Shape has a greater impact on the deposition rate than particle size or particle concentration.